Tumour-Derived, Extracellular Microvesicles in the Treatment of Acute Renal Failure: An Experimental Study - Galina V. Seledtsova; Victor I. Seledtsov; Ayana B. Dorzhieva; Irina P. Ivanova; Tatiana S. Khabalova; Adas Darinskas; Alexei A. von Delwig (Medical Sciences)
Background/Objectives: This investigation compared the therapeutic efficacy of extracellular microvesicles (MVs) derived from murine L929 sarcoma cells and murine mesenchymal stem cells (MSCs). Methods: A mouse model of acute kidney injury (AKI) was used. Results: Both MVs from L929 cells (L929-MVs) and MSCs (MSC-MVs), unlike those obtained from murine peripheral blood mononuclear cells (PBMCs), enhanced survival rates in AKI mice and significantly improved kidney function. This was indicated by decreased levels of urine albumin and serum creatinine. Furthermore, treatment with L929-MVs and MSC-MVs elevated the proportions of CD4+CD25+FOXP3+ regulatory T cells while reducing the presence of pro-inflammatory CD4+CD44+ T cells in the spleens of AKI mice. Conclusions: the results highlight the potential of tumour-derived MVs to facilitate organ repair and exert cytoprotective immunomodulatory effects.